Fabrication of CNT/Al composites with low damage to CNTs by a novel solution-assisted wet mixing combined with powder metallurgy processing. (5th May 2016) - Liu, Z.Y.; Zhao, K.; Xiao, B.L.; Wang, W.G.; Ma, Z.Y.
Abstract: A novel solution-assisted wet mixing processing was developed to efficiently produce CNT/Al composite powders. CNTs were firstly dispersed in zwitterionic surfactant aqueous solution, and then the flaky Al powders, produced from spherical Al powders by ball milling, were mixed with the CNT solution to adsorb the dispersed CNTs in the solution. It was indicated that CNTs could be uniformly adsorbed onto the flaky Al powders and CNT/Al powders with a maximum CNT concentration of 7.5 vol% could be obtained after filtering and drying. 1.5 and 3 vol% CNT/Al composites were then fabricated using the resultant composite powders through a powder metallurgy route. CNTs with average lengths of 0.9 μm and well-retained wall structure were uniformly dispersed in the Al matrix and aligned arrangement of CNTs was achieved after hot forging. Furthermore, it was found that most of CNTs were distributed at the grain boundaries and the CNT-Al interfaces were well bonded. The strengths of the CNT/Al composites were significantly increased, which could be attributed to the efficient load transfer of CNTs. Graphical abstract: Highlights: A solution-assisted wet mixing process was developed to produce carbon nanotubes/aluminum powders. The composites reinforced by high concentrations of carbon nanotubes with little damage were produced. Carbon nanotubes were singly dispersed in aluminum matrix and aligned along the deformation direction. High strength of composites is attributed to efficient load-transfer of long carbon nanotubes.